2001
DOI: 10.1124/mol.59.6.1542
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Human Concentrative Nucleoside Transporter (hCNT1) In the Cytotoxic Action of 5[Prime]-Deoxy-5-fluorouridine, an Active Intermediate Metabolite of Capecitabine, a Novel Oral Anticancer Drug

Abstract: We attempt to identify the plasma membrane transporter involved in the uptake of 5Ј-deoxy-5-fluorouridine (5Ј-DFUR), an intermediate metabolite of capecitabine. This novel oral fluoropyrimidine is used in cancer treatments and is a direct precursor of the cytostatic agent 5Ј-fluorouracil. We also examine the role of the transporter in 5Ј-DFUR cytotoxicity. The human concentrative nucleoside transporter (hCNT1) was cloned from human fetal liver and expressed in Xenopus laevis oocytes. The two-electrode voltage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 22 publications
4
66
0
2
Order By: Relevance
“…highly sensitized to nucleoside-derived cytotoxic drugs simply by heterologously expressing a CNT isoform, irrespective of whether they were also substrates for the ENT carriers already expressed (41). Moreover, it is well established that high affinity neurotransmitter transporters are involved in the modulation of neurotransmitter availability to receptors in synaptic transmission (42,43), which further supports the view that high affinity transporters are better regulators of agonist availability than low affinity carriers.…”
Section: ; This Study)supporting
confidence: 50%
“…highly sensitized to nucleoside-derived cytotoxic drugs simply by heterologously expressing a CNT isoform, irrespective of whether they were also substrates for the ENT carriers already expressed (41). Moreover, it is well established that high affinity neurotransmitter transporters are involved in the modulation of neurotransmitter availability to receptors in synaptic transmission (42,43), which further supports the view that high affinity transporters are better regulators of agonist availability than low affinity carriers.…”
Section: ; This Study)supporting
confidence: 50%
“…A major role for hENT1 in gemcitabine toxicity was demonstrated by addition of dipyridamole, a potent inhibitor of hENT1 activity, to culture media, which conferred resistance to gemcitabine by reducing the cellular uptake of gemcitabine. Mata et al (2001) showed that hCNT1 was important for cytotoxicity to capecitabine. 5 0 -Deoxy-5-fluorouridine, the active metabolite of capecitabine, is a permeant for hCNT1 and the presence of hCNT1 conferred sensitivity of CHO-K1 cells to 5 0 -deoxy-5-fluoruridine.…”
Section: Nts and Sensitivity To Nucleoside Analogsmentioning
confidence: 99%
“…Heterologous expression of hCNT1 in nonlymphoid cells increases sensitivity to 5-DFUR, a fluoropyrimidine derivative recognized by the transporter. 43 Similarly, the acquisition of hCNT2 function by gene transfer into a drugresistant T-lymphoblast cell line devoid of nucleoside transporter activity increased sensitivity to halogenated uridine analogues. 79 The role of CNT isoforms in nucleoside-derived drug anticancer therapy remains unclear, but it is likely that the two nucleoside influx pathways contribute to drug cytotoxicity.…”
Section: What Role Do Nucleoside Transporters Play In Nucleoside-derimentioning
confidence: 99%
“…This is relevant because this transporter is responsible for the high-affinity uptake of various fluoropyrimidines, including the capecitabine intermediate 5 0 -deoxy-5-fluorouridine (5-DFUR), a direct precursor of the anticancer drug 5-fluorouracil (5-FU). 41,43 Leukaemia cell lines such as NB4, Raji and BLS1 also show a Na-dependent, guanosine preferring, nucleoside transport activity that appears to be highly sensitive to inhibition by the analogue NBTI, 47,56,57 a unique property among putative CNT transporters. Nevertheless, no cDNA related to this transport activity has been isolated so far and there is no evidence that additional SLC28 members remain to be discovered.…”
Section: Nucleoside Transporters In Cllmentioning
confidence: 99%
See 1 more Smart Citation